(untitled) (Research, Society and Development, 2022)
Introduction: Intensive care units (ICU) are dedicated to the care of critically ill patients at all levels of care. Inserted in this context, the action of the qualified dentist in the ICUs is fundamental in the quality of life and in the health promotion of hospitalized patients, thus making a differentiation in the hospital care provided. Objective: to discuss the need for the presence and inclusion of the dentist in the Intensive Care Units in the face of possible dangers related to hygiene to which patients are exposed. Methodology: The works were carefully chosen following a flowchart according to Prisma’s methods. The studies were selected according to what the PRISMA flowchart proposes, which is divided into five stages of evaluation and investigation: identification, screening, eligibility, inclusion and data analysis. Results: A total of thirteen articles published in national and international journals were obtained. The results of the respective authors were analyzed in relation to the guiding question of the work. Discussion: protocols and lack of standardization are the biggest problems detected. Conclusion: the performance is still quite irregular, there is no standardization in the provision of service. Another point observed, perhaps the main one, is in relation to protocols. It was found that most hospitals do not have a culture of protocols for oral care for patients in ICUs, in some hospitals there are neither protocols nor the presence of a dental surgeon.